Pengaruh Perbandingan Kacang Hijau Dan Wijen Giling Terhadap Kadar Kalsium Dan Daya Terima Sari Kacang Hijau - Dewi, Niken Dyah Rahmawati, Pramudya Kurnia, STP., M.Agr, Endang Nur W.,SST.,M.Si.,Med (2017)
Background: Lack of calcium in adolescents and early adulthood increases the risk of osteoporosis. MOH Nutrition Research Agency in 2006, showed the prevalence rate of 10.3% of Indonesia's population are at risk for osteoporosis. One way to prevent osteoporosis is to consume foods high in calcium. One way to prevent osteoporosis is to consume cow's milk. The problem is the price of cow's milk is expensive, so one alternative is to drink mung bean concentate. Mung bean concentate has enough calcium. Besides, sesame has high calcium content to increase the calcium content of mung bean. Objective: To determine the effect of mung bean with sesame comparison milled in improving the quality of concentrate mung bean extract in terms of the level of calcium and acceptability. Methods: The experimental research design with a completely randomized design (CRD) with 3 treatments and 1 control with three repetitions. Comparisons were milled sesame, ie 0%, 5%, 10% and 15%. Determination of calcium levels using AAS method. Test acceptability concentrate mung bean carried out on 30 panelists. Statistical test calcium levels by Annova acceptability by Kruskal Wallis test and continued with Duncan test. Results: The optimal calcium levels found in the treatment of mung bean and sesame milled 85%: 15%. In the level of preference, 10% of sesame is the most preferred products. Conclusion: There is significant effect of mung beans with sesame milled to calcium and acceptability of mung bean concentrate. Keywords: concentrate of mung bean, milled sesame, calcium levels, acceptability